PERLINDUNGAN HUKUM TERHADAP RESELLER TERKAIT OVERCLAIM PRODUK SKINCARE DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Adika Riski Adiguna; Yuniar Rahmatiar; Muhamad Abas (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The cosmetics industry in Indonesia, especially skincare products, is experiencing rapid growth along with technological advances. Manufacturers are expanding their marketing through sales partnerships such as the reseller system. However, intense competition raises issues related to unethical marketing practices, such as overclaiming. One of the viral cases of Daviena Skincare brand skincare products, Retinol booster skincare products are claimed to contain 2% Actosome Retinol but laboratory test results show only 0.03%. Another product, HB Dosting 7×, claims to contain Niacinamide, but laboratory test results did not detect the content or 0%. This overclaim caused losses to Daviena skincare resellers because they experienced a significant decline in sales, this is contrary to Law No. 8 of 1999 concerning Consumer Protection. This study aims to analyze legal protection for resellers and producer responsibility in overclaim cases. The research method used is normative juridical with statutory and conceptual approaches. The results showed that legal protection for resellers is in the form of product recalls and renewal of skincare product formulas by manufacturers. In addition, the manufacturer provides compensation in the form of a refund to reseller partners who have returned overclaimed products to the Daviena Skincare central warehouse.